ANALYSIS OF THE RELATIONSHIP BETWEEN APRI SCORE AND THE DEGREE OF ESOPHAGEAL VARICES IN LIVER CIRRHOSIS PATIENTS AT RSUD PROF. DR. MARGONO SOEKARJO - Wijayana, Kamal; Putra, Fadhly Nino; Djatmiko, Wahyu; Siswandari, Wahyu; Magfiroh, Nisaul (Medical and Health Journal, 2025)
Esophageal varices are one of the most common complications in patients with liver cirrhosis and can lead to high-risk bleeding. This study aims to analyze the relationship between the APRI (Aspartate Aminotransferase-to-Platelet Ratio Index) score and the degree of esophageal varices in liver cirrhosis patients at RSUD Prof. Dr. Margono Soekarjo. This research used an observational analytic design with a cross-sectional approach, involving 89 patients who met the inclusion criteria. The analysis revealed a significant positive correlation between the APRI score and the degree of esophageal varices (p=0.039, r=0.220), indicating that the higher the degree of esophageal varices, the higher the APRI score. These findings suggest that the APRI score can be used as a non-invasive tool to detect the degree of esophageal varices in liver cirrhosis patients, with potential as a more practical and cost-effective diagnostic method